I contributi delle scienze umane all'interpretazione della fiaba: dall'antropologia alla psicoanalisi... con tracce filosofiche - Rossella Certini (Firenze University Press, 2017)
The tale has undeniable anthropologic and psychoanalytic connotations. The contribution of human sciences about tales symbolism is acknowledged, but it always needs to be defined and thought again.  Starting with the classic texts by Vladimir Propp, Bruno Bettelheim, Carl G. Jung, Marie-Louise Von Franz, the es-say addresses the typical themes of this narrative tipology: the historical and ar-chetypal origins of the tale, its characters and its adventure sites, the intra-psychic implications that make it a hermeneutic instrument for better interpreting the ex-istential needs of the reader (and the writer). In the final part of the essay, an orig-inal note linked to the philosophical reflection of Soren Kierkegaard. Very young, the Danish philosopher has come up with an essay on art to tell the tales, where he emphasizes the importance to link the child to the poetic vision of the narration. These positions and authors are interpreted in a pedagogical way.